COMPARISON OF KETAMINE AND TRAMADOL FOR PREVENTION OF SHIVERING DURING SPINAL ANESTHESIA - AVAIS, B; JAVED, HM; SHEIKH, NG; SHEIKH, MG; JAMSHAID, B; BUTT, Z (Biological and Clinical Sciences Research Journal, 2022)
After receiving a spinal anesthetic, shivering is a common side effect. This research aimed to compare the effectiveness of Ketamine and Tramadol in reducing the occurrence of shivering. One hundred and fifty patients aged 18 to 60 with ASA physical status I or II having different surgical procedures were randomly assigned to receive either Intravenous (IV) normal saline (Group P), IV 0.5mg/kg ketamine (Group K), or IV 0.5kg/mg tramadol (Group T).The frequency of shivering, its impact, and the onset of nausea, vomiting, sweating, and nystagmus were all noted. Patients were similar in demographics, body temperature at baseline, operation type, median sensory blockage, surgery duration, and anesthetic. 23.3% of patients (35/150) experienced shivering episodes.Twenty-twopatientsin the placebo group, followed by eight in treatment Group T, and five in treatment group K, reported shivering. The study revealed a statistically significant difference (p = 0.006) between Group K and P. When comparing Group T to Group K (p = 0.871) and Group P (p = 0.724), however, no group showed statistical significance. In group K, nystagmus was one of the most commonly reported adverse effects of IV ketamine, affecting 35 patients (70%). Therefore, compared to the placebo group, Ketamine at a dose of 0.5mg/kg reduces the shivering associated with spinal anesthesia. But there was no statistically significant difference between Ketamine and the intravenous 0.5 mg/kg Tramadolgroup found in our study.